A Web services accessible database of turbulent channel flow and its use for testing a new integral wall model for LES. Issue 2 (1st February 2016) - Graham, J.; Kanov, K.; Yang, X. I. A.; Lee, M.; Malaya, N.; Lalescu, C. C.; Burns, R.; Eyink, G.; Szalay, A.; Moser, R. D.; Meneveau, C.
Abstract: The output from a direct numerical simulation (DNS) of turbulent channel flow at Re τ ≈ 1000 is used to construct a publicly and Web services accessible, spatio-temporal database for this flow. The simulated channel has a size of 8π h × 2 h × 3π h, where h is the channel half-height. Data are stored at 2048 × 512 × 1536 spatial grid points for a total of 4000 time samples every 5 time steps of the DNS. These cover an entire channel flow-through time, i.e. the time it takes to traverse the entire channel length 8π h at the mean velocity of the bulk flow. Users can access the database through an interface that is based on the Web services model and perform numerical experiments on the slightly over 100 terabytes (TB) DNS data on their remote platforms, such as laptops or local desktops. Additional technical details about the pressure calculation, database interpolation, and differentiation tools are provided in several appendices. As a sample application of the channel flow database, we use it to conduct an a-priori test of a recently introduced integral wall model for large eddy simulation of wall-bounded turbulent flow. The results are compared with those of the equilibrium wall model, showing the strengths of the integral wall model as compared to the equilibrium model.